The war criminals investigate - Schuhmacher, J (2017)
This thesis uses the war crimes investigations carried out by the Wehrmacht between 1939- 1945 to explore the creation and development of the narrative which the Nazi regime constructed to justify its war of aggression, conquest, and extermination. This source has been sorely underused and provides deep insight into the regime’s official narrative – a narrative which seems fundamentally at odds with its true aims and its murderous actions. It claimed that the Reich was waging a war in self-defence and for humanitarian reasons. These justifications were designed to convince both the German population and international audiences. The regime did not simply lie, however, but gathered empirical evidence which it then used selectively to legitimise the war. By reconstructing this process, the thesis aims to understand the degree to which the regime was able to make its arguments convincing. This allows us to better understand how it was possible to mobilise so many ordinary Germans to support and fight the war and, indeed, to perpetrate horrendous crimes. In particular, this thesis seeks to explore the tension between the official narrative and the Reich’s own crimes, arguing that these two were not diametrically opposed, but that there was a direct justificatory link between them. Crucial in this context was the degree to which the regime could portray its criminal actions as a response to those of the enemy. In doing so, this thesis develops on a historiography which has acknowledged the importance of the regime’s justificatory framework, but which has yet to study the foundations on which this was based and how it developed over the course of the war. In short, this is a study of the German narrative of victimhood which underpinned the brutal war of extermination.